1986
DOI: 10.1113/jphysiol.1986.sp016086
|View full text |Cite
|
Sign up to set email alerts
|

The effects of anaesthetics and high pressure on the responses of the rat superior cervical ganglion in vitro.

Abstract: SUMMARY1. The effects of helium pressure and of general anaesthetics were studied on the responses of the isolated superior cervical ganglion of the rat, to determine how far these reflected the pressure reversal of anaesthesia seen in vivo. The method of Brown & Marsh (1974) for extracellular recording of surface potentials was adapted for use in a high-pressure chamber.2. Helium alone, at 130 atm, did not alter the responses of the ganglion to y-aminobutyric acid (GABA) but significantly depressed the depola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Although a lack of effect of N 2 O on GABA A receptors has been reported previously (Little and Thomas, 1986), a recent paper using isolated hippocampal neurons and a local perfusion system similar to that used here found potentiation of responses to exogenously applied muscimol (Dzoljic and Duiijn, 1998). Similarly, a study of invertebrate glutamate receptors reported blockade by N 2 O (Macdonald and Ramsey, 1995).…”
Section: Discussionmentioning
confidence: 82%
“…Although a lack of effect of N 2 O on GABA A receptors has been reported previously (Little and Thomas, 1986), a recent paper using isolated hippocampal neurons and a local perfusion system similar to that used here found potentiation of responses to exogenously applied muscimol (Dzoljic and Duiijn, 1998). Similarly, a study of invertebrate glutamate receptors reported blockade by N 2 O (Macdonald and Ramsey, 1995).…”
Section: Discussionmentioning
confidence: 82%
“…Little of the protein receptor work has approached this peculiar property of GAs. Is it an effect at the level of the whole CNS ( Halsey, 1982 ; Little and Thomas, 1986) , or is it an effect at the molecular level ( Trudell et al ., 1973a , b ; 1975 ; Chau et al ., 2007 ; 2009 )? Recent research has swung towards a protein receptor for GAs, and the evidence is quite persuasive.…”
Section: Future Directionsmentioning
confidence: 99%
“…Pressure reversal was observed in the action potential in peripheral nerves: high-pressure helium, itself shown not to affect nerve conduction, reversed the reduced action potential height caused by anaesthetics ( Roth et al ., 1976) . The site of action was not the sympathetic nerves in the superior cervical ganglion ( Kendig et al ., 1975) ; nor the neuromuscular junction ( Kendig and Cohen, 1976) ; nor the effect caused by a combination of pentobarbitone, N 2 O or high-pressure N 2 gas and GABA on its receptors ( Little and Thomas, 1986) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations